2005
DOI: 10.1111/j.1551-2916.2005.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Investigation of the Aging Behavior of (3Y‐TZP)–Al2O3 Composites

Abstract: The low temperature autoclave aging behavior of zirconia toughened alumina composites processed by a classical powder mixing processing route was analyzed using atomic force microscopy (AFM), scanning electron microscopy and X-Ray diffraction. The transformation was evaluated in terms of nucleation and growth, assessed by XRD. The time-temperature equivalency of the transformation was used to measure an apparent activation energy of the nucleation stage of the transformation of 78 kJ/mol. The microstructural f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 28 publications
(61 reference statements)
6
52
0
1
Order By: Relevance
“…This size for Y-TZP under hydrothermal conditions is reportedly less than 360 nm [204]. Deville et al confirmed that small ZrO 2 grains <500 nm are also required in ZTA ceramics [205], with the Al 2 O 3 matrix influencing their critical transformation size. Typically, the t-ZrO 2 grains are located at alumina grain boundaries or at triple-point grain junctions [206]; but unique intragranular composites have been developed having submicron Al 2 O 3 /t-ZrO 2 grains embedded within larger Al 2 O 3 grains [207].…”
Section: Grain Size and Morphologymentioning
confidence: 90%
See 3 more Smart Citations
“…This size for Y-TZP under hydrothermal conditions is reportedly less than 360 nm [204]. Deville et al confirmed that small ZrO 2 grains <500 nm are also required in ZTA ceramics [205], with the Al 2 O 3 matrix influencing their critical transformation size. Typically, the t-ZrO 2 grains are located at alumina grain boundaries or at triple-point grain junctions [206]; but unique intragranular composites have been developed having submicron Al 2 O 3 /t-ZrO 2 grains embedded within larger Al 2 O 3 grains [207].…”
Section: Grain Size and Morphologymentioning
confidence: 90%
“…Remarkably, they reported no increase in monoclinic content and no observable degradation for either composition. Later, Deville et al published two studies on the low-temperature ageing of ZTA [205,459]. Their first paper examined a range of Al 2 O 3 -ZrO 2 compositions from 2.5 wt.% ZrO 2 in Al 2 O 3 to pure 3Y-TZP.…”
Section: Hydrothermal Stabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…In some applications, like the femoral head implants, the increase of the surface implant roughness and microcraking due to a transformation of specific agglomerated zirconia grains can have a dramatic effect on their life span. 22 Therefore, the presence of zirconia aggregates, especially if the zirconia is stabilized with yttria, should be avoided. 23 Experiments carried out by many researchers 24,25 have shown that the mechanical properties and wear of alumina can be significantly enhanced by the dispersion of ceramic particles in the nanometer size range.…”
mentioning
confidence: 99%